Modulation of Antigen-Specific T-Cells as Immune Therapy for Chronic Infectious Diseases and Cancer - Li, Suling; Symonds, Alistair L. J.; Miao, Tizong; Sanderson, Ian; Wang, Ping (Frontiers in Immunology, 2014)
T cell responses are induced by antigen presenting cells (APC) and signals from the microenvironment. Antigen persistence and inflammatory microenvironments in chronic infections and cancer can induce a tolerant state in T cells resulting in hyporesponsiveness, loss of effector function and weak biochemical signalling patterns in response to antigen stimulation. Although the mechanisms of T cell tolerance induced in chronic infection and cancer may differ from those involved in tolerance to self-antigen, the impaired proliferation and production of IL-2 in response to antigen stimulation are hallmarks of all tolerant T cells. In this review, we will summarize the evidence that the immune responses change from non-self to "self"-like in chronic infection and cancer, and will provide an overview of strategies for re-balancing the immune response of antigen specific T cells in chronic infection and cancer without affecting the homeostasis of the immune system.